A valuable or a curse resource? A systematic review on expansion, perception of local community, benefits and side effects of Prosopis juliflora - Eshetu, Amogne Asfaw (Frontiers in Conservation Science, 2024)
IntroductionProsopis juliflora has posed a severe threat to human and animal life in arid and semi-arid areas of the world. Thus, this review intends to shed light on the potential use of Prosopis as a helpful resource and feasible management system.MethodsThis research employs a systematic review methodology.ResultsThe review revealed that the species had been introduced to overcome deforestation and desertification. Prosopis juliflora has had different socioeconomic and environmental impacts on local communities. The most widely cited adverse impacts include out-competing native species and quickly reducing forage plants, being a harbour for predators, health problems and death of domestic animals, and being an ideal ground for mosquito breeding. On the other hand, the species provides multiple ecosystem services like the provision of construction materials, animal feed and charcoal; plays a role in soil conservation and rehabilitation of degraded and saline soils, good sources of nectar for honey production; contributes to reducing dust pollution; enhances carbon sequestration, and have medicinal value due to its antifungal and antibacterial features. The local community’s attitude regarding the species is mixed.DiscussionThe consequent negative impacts are increasing quickly, making the urgent need to develop robust and practical management strategies necessary to both mitigate the adverse effects and fully use the benefits. Commercialization (with a notion of management through utilization) is a feasible way to minimize expansion. Cross-boundary endeavours for controlling Prosopis juliflora expansion to new regions, particularly in countries predicted as edges of high potential invasion, are required to manage the species invasion efficiently.